2005
DOI: 10.1002/mame.200500296
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Nano‐Structured Polyaniline Composite Film via “Carbon Nanotubes Seeding” Approach and its Gas‐Response Studies

Abstract: Summary: Polyaniline composite film with nano‐structure was prepared through a chemical oxidation method by adding carbon nanotubes (CNTs) as nano‐fiber seeds. Spin‐coating or casting method was employed on the interdigital electrodes of carbon and the composite film was formed with an in‐situ polymerization approach. The gas‐response to trimethylamine was also examined at room temperature. It was found that the difference was not only in the morphology, but also in the value of gas‐sensitivity. Comparing with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 32 publications
1
21
0
1
Order By: Relevance
“…These materials find potential applications as sensors, UV detectors, catalysts, biosensors, and piezoelectronic materials [14]. As with conventional composites, the properties of nanocomposites can display synergistic improvements over those of the component phases individually.…”
Section: Introductionmentioning
confidence: 99%
“…These materials find potential applications as sensors, UV detectors, catalysts, biosensors, and piezoelectronic materials [14]. As with conventional composites, the properties of nanocomposites can display synergistic improvements over those of the component phases individually.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of fabrication, the focus is on the embedding or incorporation of the CNTs into the bulk polymer, with polymerization of the bulk polymer by conventional means, including chemical [63][64][65][66][67][68], electrochemical [69][70][71], photopolymerisation [72,73]and vapor deposition [74]. So, clearly, the main focus of the evaluation of the nanocompsites is the enhancement brought by the incorporation of CNTs into traditional bulk materials.…”
Section: Carbon Nanotube Nanocompositesmentioning
confidence: 99%
“…So, clearly, the main focus of the evaluation of the nanocompsites is the enhancement brought by the incorporation of CNTs into traditional bulk materials. As well as more obvious enhancements in the conductivity of the composite films over conducting polymer alone, it has also been suggested that polymerization in the presence of the CNTs alters the polymerization process, leading to templating and growth orientation [75,63]. A PPy-SWNT conductimetric sensor for NO 2 detection was shown to be of comparative sensitivity to SWNTs alone when the composite was spin-cast and chemically polymerized [66] with a sensitivity of 0.9 at 3000 ppm.…”
Section: Carbon Nanotube Nanocompositesmentioning
confidence: 99%
See 1 more Smart Citation
“…So nanostructured materials and nano/micro-electronic devices have received considerable attention to result in great progress [1][2][3][4][5][6][7]. The researches on nanostructured material, including organic materials [5][6][7][8][9][10][11][12], inorganic materials [1][2][3][4] and organic-inorganic hybrid materials [13][14][15][16][17][18][19][20], reveals that organic materials are promising because of their simple preparation, easy modification, convenient morphology tailoring and some special functional properties. Nano-structured conductive polymers are one kind of important typical functional materials, they have potential applications in many fields, such as lightweight battery electrode, display devices, organic flexible conductor, electronic newspaper, electromagnetic shielding device, anticorrosion coatings, chemical sensors and biosensors [5,6].…”
Section: Introductionmentioning
confidence: 99%